Deep groundwater circulation through the High Arctic cryosphere forms Mars-like gullies - Grasby, S.; Proemse, Bernadette; Beauchamp, B. (Geological Society of America, 2014)
We report here the discovery of the northernmost known perennial spring, located in the polar desert of the Canadian High Arctic (average precipitation 75.5 mm/yr; average annual air temperature –19.7 °C). The high-discharge spring (~520 L/s) has also anomalously high temperatures (9.0 °C), despite occurring in a region of low geothermal gradient and thick (>400 m) permafrost. Active erosion at the spring outlet forms gullies with alcove-channel-apron morphology, remarkably similar to archetypal gullies observed on mid-latitude regions of Mars. Geochemical and isotopic data show a meteoric origin for the waters, demonstrating that deep circulating groundwater systems can form active connections through the cryosphere to the subsurface, even in the absence of thermal anomalies. This discovery challenges current understanding of high-latitude permafrost hydrology.